OLYMPUS: An emission model to connect urban form, individual practices and atmospheric pollutant release. (15th January 2021) - Elessa Etuman, Arthur; Coll, Isabelle; Rivera Salas, Virna
Abstract: At a time when many cities are rethinking their development and urban planning policies in order to cope with new economic, societal and environmental paradigms, the question arises as to which public policies should be favored in order to achieve current and future air quality objectives. Decision support for urban air pollution control can no longer rely solely on improved technologies, but must propose new modelling approaches that integrate urban organization, the individual and energy consumption practices. In this paper, we present the operating principles of the OLYMPUS model and discuss the results obtained during its implementation in two distinct territories. OLYMPUS is an activity-based model that - for a given urban organization - simulates the gaseous and particulate emissions related to the energy consumption of individuals for their mobility, combustion from residential heating, domestic activities and commercial building heating. The very heart of the simulation is to define, prioritize and spatialize the daily mobility of individuals, as well as to define the energy demand per building. The results are presented here for Ile-de-France - a dense metropolis highly served by public transport, housing 12 million inhabitants - and the Pays de la Loire - a polycentric urban area organized around medium-sized towns within a highly rural space. By implementing OLYMPUS on these two different territories, we demonstrate the very good transposability of the tool. In parallel, we propose a discussion of the parameters that most constrain the emissions in the model, and the opportunities for innovative scenarios dedicated to decision support.